2004
DOI: 10.1190/1.1707053
|View full text |Cite
|
Sign up to set email alerts
|

VSP traveltime inversion: Near‐surface issues

Abstract: P-wave velocity information obtained from vertical seismic profiles (VSPs) can be useful in imaging subsurface structure, either by directly detecting changes in the subsurface or as an aid to the interpretation of seismic reflection data. In the shallow subsurface, P-wave velocity can change by nearly an order of magnitude over a short distance, so curved rays are needed to accurately model VSP traveltimes. We used a curved-ray inversion to estimate the velocity profile and the discrepancy principle to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…7(b) is the virtual refraction. The virtual refraction has an average velocity v 1 = 2700 m/s, which agrees well with the P‐wave speed in saturated sand (Moret et al 2004). This is the identical moveout speed as the refraction speed in the real shot record.…”
Section: Surveysupporting
confidence: 70%
“…7(b) is the virtual refraction. The virtual refraction has an average velocity v 1 = 2700 m/s, which agrees well with the P‐wave speed in saturated sand (Moret et al 2004). This is the identical moveout speed as the refraction speed in the real shot record.…”
Section: Surveysupporting
confidence: 70%
“…[], for further information on well construction, and details about positive well skin). Stratigraphic units at the BHRS (Figure ) have been defined based initially on distributions of porosity estimated from neutron logs and grain‐size characteristics from core [ Barrash and Clemo , ; Reboulet and Barrash , ; Barrash and Reboulet , ], and similar structures have been recognized through analysis of ground‐penetrating radar (GPR) [ Clement et al ., ; Clement and Barrash , ; Clement and Knoll , ; Irving et al ., ; Ernst et al ., ; Bradford et al ., ; Dafflon et al ., ], seismic [ Moret et al ., ], and capacitive conductivity [ Mwenifumbo et al ., ] surveys.…”
Section: Field Site and Data Collectionmentioning
confidence: 99%
“…The regularized inversion that lies at the heart of Occam’s approach also allows for an independent estimation of data error based on the discrepancy principle (Hansen ; Moret et al ) that is purely based on the characteristics of the regularized slowness inversion. Hansen () found that a function ν(λ) can be defined as a combination of the elements of the regularized inversion objective function, where λ is the regularization parameter, i.e., the weight of the smoothness constraint with respect to the fit of the data.…”
Section: Methodology: Vertical Radar Profilesmentioning
confidence: 99%